Estimasi Permintaan Agregat Regional Provinsi Jambi (Pendekatan Model Makro Ekonomi) - Hurriyah Huriyah; Syamsurijal Tan; Amril Amril (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2013)
The research objective was to analyzing fluctuations in aggregate demand growth variables are C, I, G, X, M and also regional gross domestic product for the year 1993-2010. To calculate and analyze some of the factors that affect the change of macro-regional components of aggregate demand in the years 1993-2010 Jambi Province. During the period 1993-2010 the economic growth rate Jambi average of 5 percent annually. Partially visible growth of household consumption by 23 percent investment by 18 per cent, 26 per cent of government spending, net exports of 43 percent. For calculate and analyze some factor that affect the change, here using regression equation with non log and log. Keywords: economic growth, consumption, investment, government spending, net exports